Analisis Strategi Sosial Marketing Dalam Meningkatkan Volume Penjualan - Zuhdi, Saefudin; Syarif, Rini (Jurnal Ilmiah Manajemen Kesatuan, 2013)
In effort to prevent HIV/AIDS, condom is an alternative to prevent HIV transmission from sexual relations. As a prevention tool, condom has not been 100% safe yet. Moreover, there is a controversial information about porous condom.In marketing the product, that is condom, particularly for high risk group, Himpunan Abiasa applys social marketing strategy. In addition to knowing which marketing strategy is applied, the author can find out the volume of Kondom Sutra sales marketed via social marketing during the period 2009 – 2010. The research method used is Descriptive Analysis and SWOT Analysis. Data utilized are primary data and secondary data: looking for and collecting data from Himpunan Abiasa, NAC (National AIDS Commision), company profile, books, and literatures related to the study; besides that, by interviewing four experts having competence in their field. By using SWOT analysis, the researcher gets internal matrix score : 2626 and external matrix score : 2677. It shows that the company has growth and stabilization, the company keeps be able to maintain existing business in continuity. This writing is a form of acknowledgement and appreciation to the company on what it has been applied. Besides that, the author gets benefit by the fact that he can enlarge knowledge concerning the application of social marketing as a strategy of HIV-AIDS prevention program. Keywords: marketing strategy; social marketing; sales volume